EKSPLORASI ETNOMATEMATIKA ANYAMAN TIKAR DI DESA RAPOWAWO KECAMATAN NANGAPANDA KABUPATEN ENDE - Yohanes Roimus Sewa; Agustina Mei; Maria Goreti Diciloam Bantas (Program Studi Pendidikan Matematika, 2023)
The surrounding culture can be used as teaching material in mathematics. Culture-based mathematics learning is called ethnomathematics. One form of culture of the people of Rapowawo Village. This study aims to explore and obtain information about mathematical concepts and mathematical elements contained in woven mats in Rapowawo Village, Nangapanda District, Ende Regency. The type of research used in this research is descriptive qualitative research with an ethnographic approach. Data was obtained through observation, interviews and documentation. The data validity technique used is a triangulation of data sources. The results of this study indicate that the woven mats in Rapowawo Village contain mathematical concepts and elements. Mathematical concepts contained in woven mats in Rapowawo Village, Nangapanda District, Ende Regency, namely geometric concepts including; points, lines, angles, and plane figures as well as equivalent ratios and arithmetic sequences. This study only examines the procedures and results of woven mats in Rapowawo Village, Nangapanda District, Ende Regency, then it is recommended to make teaching materials so that they can be applied to learning.